2022
DOI: 10.3390/ijerph191610083
|View full text |Cite
|
Sign up to set email alerts
|

Does the Association of Sedentary Time or Fruit/Vegetable Intake with Central Obesity Depend on Menopausal Status among Women?

Abstract: (1) Background: The prevalence of central obesity is growing rapidly among women, and the prevalence differs by menopausal status. Longer sedentary time and less fruit/vegetable (F/V) intake increased the risk of central obesity. Among women of different menopausal statuses, controversy surrounds the association between sedentary time or F/V intake and central obesity. This study aimed to explore whether the independent and joint associations between sedentary time or F/V intake and menopausal status are corre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…The EFDP focuses mainly on fruit, eggs, and fish. The intake of fruits is associated with the improvement of obesity indicators [64] and can reduce the risk of central obesity [65], while the intake of eggs can reduce hunger [66] and significantly reduce short-term energy intake in children [67]. Additionally, the advantages of fish have been fully stated above.…”
Section: Discussionmentioning
confidence: 99%
“…The EFDP focuses mainly on fruit, eggs, and fish. The intake of fruits is associated with the improvement of obesity indicators [64] and can reduce the risk of central obesity [65], while the intake of eggs can reduce hunger [66] and significantly reduce short-term energy intake in children [67]. Additionally, the advantages of fish have been fully stated above.…”
Section: Discussionmentioning
confidence: 99%
“…Existing studies have explored the relationship between obesity, weight gain, and breast cancer risk in pre-menopausal women, indicating that adult weight gain may increase post-menopausal breast cancer risk among women with lower body mass index at a younger age (Renehan et al, 2020). Dietary factors have also been studied, with findings showing that higher fruit and vegetable intake is associated with a lower risk of central obesity among pre-menopausal women (Su et al, 2022). Structural equation model analysis has revealed significant differences in body fat percentage and visceral fat area between menopausal and pre/perimenopausal women, highlighting the impact of menopausal status on obesity-related factors (Darbandi et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Studies on the level of inactivity and public health showed that the increase in inactivity is associated with the increase in obesity, as well as decrease in physical activity with a decrease in general health ( McCoy and Morgan, 2020 ). Research related to the level of mobility in different stratum of society has progressed such that it has been shown that the effect of the education level on food intake, obesity and other health risk factors (mobility level) has changed over time ( Su et al, 2022 ). In addition to the fact that regular physical activity leads to an increase in physical readiness, it has been shown that there is a significant relationship between high physical readiness and high self-esteem ( Reddy et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Research related to the level of mobility in different stratum of society has progressed such that it has been shown that the effect of the education level on food intake, obesity and other health risk factors (mobility level) has changed over time (Su et al, 2022). In addition to the fact that regular physical activity leads to an increase in physical readiness, it has been shown that there is a significant relationship between high physical readiness and high self-esteem (Reddy et al, 2021).…”
Section: Introductionmentioning
confidence: 99%